Load to failure of three different monolithic zirconia inlay- retained fixed dental prosthesis designs with three surface treatments - Samhan, Talaat Mohamed; Zaghloul, Hanaa (Brazilian Dental Science, 2020)
Objective: The purpose of the study was to evaluate the effect of different preparation designs and different surface treatments on the fracture resistance of monolithic zirconia inlay-retained fixed dental prosthesis [IRFDP]. Material and methods: Forty-five translucent zirconia IRFDPs were divided into three groups according to preparation designs (n = 15); group I: proximal box, group II: inlay-box and group III: butterfly wing (modified inlay). Each group was further subdivided into three subgroups according to the surface treatments utilized (n = 5); sandblasting, tribochemical silica coating (Cojet system) and erbium, chromium: Yttrium, scandium, gallium, garnet (Er, Cr: YSGG) laser irradiation. All zirconia IRFDPs were cemented to their respective resin models using selfadhesive resin cement. All cemented IRFDPs were subjected to fracture resistance test using universal testing machine. The initial fracture site was determined by using a stereomicroscope (x6.7magnification). Two-way analysis of variance (ANOVA) was used to evaluate the effect of different designs, different surface treatments and their interaction on the mean fracture resistance. Bonferroni’s post-hoc test was used when ANOVA is significant (P ? 0.05). Results: Butterfly wings design showed the highest fracture resistance values followed by inlay and box designs respectively (P ? 0.05). Sandblasting and Cojet showed significantly the highest mean fracture resistance values than Laser with no significance difference between them. Conclusion: The butterfly wing design increased the fracture resistance of the zirconia IRFDPs. Sandblasting and tribochemical silica coating of zirconia surfaces had a greater effect than Er, Cr: YSGG laser to gain higher fracture resistance of zirconia IRRDPs. KEYWORDS Inlay-retained FDPs; Monolithic zirconia; Preparation designs; Surface treatments; fracture resistance.